PWE-082 Decrease in parietal cell density at squamo-columnar junction with increasing age in asymptomatic healthy volunteers. (23rd September 2015) - Seenan, J P; Derakhshan, M H; Wirz, A A; Clarke, A T; Kelman, A W; Going, J J; McColl, K E L
Abstract : Introduction: The gastric cardia is an important site of pathology with a high incidence of inflammation, metaplasia and neoplasia. However the area is poorly understood and cardia mucosa may itself be pathological. Previous autopsy studies show a near absence of cardia epithelium in neonates and an increase in length with age. Aims: To 1 investigate whether parietal cell density in the columnar mucosa at the squamocolumnar junction (SCJ) changes with age and 2 determine the association of parietal cell density with distal oesophageal acid exposure. Methods: 25 healthy volunteers (14 males, 5 Helicobacter pylori positive) were studied. Biopsies were taken from the macroscopic SCJ, 1 cm distal to the SCJ, gastric body and antrum. Biopsies were embedded in paraffin and 5-micron sections cut for immunohistochemistry. Parietal cells were stained and visualised using a standardised monoclonal anti-H+/K+ATPase antibody. Slides were digitally scanned and uploaded onto a slide server. An image analysis programme was used to quantify parietal cell density expressed as intracellular positive pixels. The average parietal cell density in a minimum of four sections of columnar mucosa per slide was reported as the percentage of the total cells per section. In 20 subjects pH studies were performed before and after a standardised meal. Acid exposure was calculated as per cent time pH<4. Spearman's σ correlation and Mann-Whitney U tests were used for analysis of non-parametric data. Results: There was a significant negative correlation between age and parietal cell density in the columnar mucosa at the level of the SCJ (R=−0.530, p=0.008). There was no significant correlation between age and parietal cell density 1 cm distal to the SCJ (R=0.153, p=0.5), in the gastric body (R=0.386, p=0.08) or antrum (R=0.117, p=0.6). In the HP negative subgroup, parietal cell density at the SCJ of volunteers under 30 years old was significantly greater than those aged 30 years and over (6.8% vs 0.4%, p=0.05). In contrast, gastric body parietal cell density was lower in the younger group (30.0% vs 34.5%, p=0.019). There was no significant correlation between distal oesophageal acid exposure and parietal cell density at the SCJ (R=0.223, p=0.3). Conclusion: Parietal cell density decreases with age in the columnar mucosa at the SCJ. This effect appears to be localised to the SCJ and is not seen 1 cm distal to this or within the stomach. There was no correlation between parietal cell density and acid exposure. These results support cardiac mucosa being acquired and due to mechanisms other than traditional gastro-oesophageal reflux.